Effects of Nitrogen Phosphorus Potassium and Sulphur on Growth Yield and Nutrient Content of Strawberry (Fragaria ananassa) (Journal of Environmental Science and Natural Resources, 2016)
The experiment was conducted at Horticulture Research Centre, Gazipur, Bangladesh, to study the effects of N, P, K, and S on growth, yield and nutrient content of strawberry following Randomized Complete Block Design (RCBD) method. There were 4 levels of different nutrients and there was a positive impact of each fertilizer combinations on yield, yield parameters and nutrient contents of BARI Strawberry except control treatment. The highest values of plant height (25.60 cm); number of leaves (21.66), flowers (125.33), fruits (12.35),destroyed fruits (11), fruit weight (215.10 g) plant-1 and fruit length (4.16 cm), fruit diameter (3.41cm), individual fruit weight (17.85 g) and fruit yield (11.50 t ha-1) were found in treatment of 115,40,110 and 25 kg ha-1NPKS, respectively. Among the fertilizers, the single effect of N (115 kg ha-1), P (40 kg ha-1), K (110 kg ha-1) and S (25 kg ha-1) gave maximum growth and yield of strawberry. The highest concentration of N, P, K and S were found in shoot and fruit of strawberry when N, P, K and S fertilizers were used 140,60,135 and 35 kg ha-1, respectively.J. Environ. Sci. & Natural Resources, 9(1): 99-108 2016